Lifting Parallel Graph Transformation Concepts to Model Transformation based on the Eclipse Modeling Framework - Biermann, Enrico; Ermel, Claudia; Taentzer, Gabriele (Electronic Communications of the EASST, 2010)
Model transformation is one of the key concepts in model-driven software development. An increasingly popular technology to define modeling languages is provided by the Eclipse Modeling Framework (EMF). Several EMF model transformation approaches have been developed, focusing on different transformation aspects. This paper proposes parallel graph transformation introduced by Ehrig and Kreowski as a suitable framework for modeling EMF model transformations with multi-object structures. Multi-object structures at transformation rule level provide a convenient way to describe the transformation of structures with a variable number of recurring structures, dependent on concrete model instances. Parallel graph transformation means the simultaneous application of a set of transformation rules synchronized at the application of a kernel rule. We apply our extended EMF model transformation technique to model the simulation of statecharts with AND-states.